Diseño Y Desarrollo Metodológico Del Funcionamiento Del Nicho Ecológico De La Demanda Del Sistema Turístico - Manuel Antonio Abarca Zaquinaula (European Scientific Journal, ESJ, 2017)
This study was designed and developed methodologically based on the operation of the ecological niche of the demand of the tourist system (based on the models of Roberto Boullón, Neil Leiper, and the World Tourism Organization). It was carried out from a systemic-mechanical approach that revolves around the well-being, health, and the decision of the demand when traveling to a tourist destination. This study however stresses that one of the main causes of mortality in the world is stress. As a result, many tourism modalities should be recipes that mitigate and/or regulate the different levels of global tourism demand. In the present essay, it was clearly explained that the faster the rotation of the two rotors of the ecological niche of the demand, the more stress accumulate their bodies. As a result of this, the acceleration will bring about the tastes, preferences, needs, demands, and tendencies of the tourists. Necessary inputs facilitates the operation and development of a destination and/or tourism system. Additionally, it allow the servers of the supply engine to adapt and/or mold to these demand inputs to achieve their satisfaction to the fullest, and also mitigates the stress that haunts them.